1983
DOI: 10.1159/000149393
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus: Detection of Viral DNA Sequences and Evidence for Molecular Heterogeneity in Metaplasias and Dysplasias of the Uterine Cervix

Abstract: Colposcopic-directed biopsies of the uterine cervix from 22 patients were analyzed for the presence of human papillomavirus (HPV) DNA and structural antigens. 11 of the biopsies were classified microscopically as mild dysplasia, 3 as moderate dysplasia, 1 as severe dysplasia, and 7 as squamous metaplasia. Nonstringent hybridization with a bovine papillomavirus type 1 DNA probe and immunocytochemical analysis with an antiserum against papillomavirus genus-specific structural antigens were performed on all speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Cellular DNA suitable for restriction enzyme digestion and subsequent Southern blot hybridization studies ( Fig. 1) was prepared by proteinase K digestion and phenol extraction as described previously (21). The nucleic acid extract (1 to 10 ,ug) was digested with restriction endonuclease PstI or BamHI (Bethesda Research Laboratories, Inc.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular DNA suitable for restriction enzyme digestion and subsequent Southern blot hybridization studies ( Fig. 1) was prepared by proteinase K digestion and phenol extraction as described previously (21). The nucleic acid extract (1 to 10 ,ug) was digested with restriction endonuclease PstI or BamHI (Bethesda Research Laboratories, Inc.).…”
mentioning
confidence: 99%
“…Hybridization and washes were modifications of a previously described procedure (21). The filters were baked under a vacuum for 30 min at 80'C and prehybridized in 4x SSC (lx SSC is 0.15 M NaCl plus 0.015 M sodium citrate) (34)-0.5 mM EDTA-10x Denhardt solution (8)-50 ,ug of tRNA per ml-20 mM sodium phosphate buffer (pH 7.4).…”
mentioning
confidence: 99%
“…cates that the NOD mouse is H-2K" and H-2Db (6). We also studied the reactivity of monoclonal antibodies to the I-A and I-E glycoprotein molecules and the interaction ofa conventional antiserum to Ia with NOD splenocytes (Table 1) (7)(8)(9)(10)(11)(12). As a control for the percentage of B lymphocytes in the spleen of each strain, we analyzed the reactivity of antimouse immunoglobulin.…”
mentioning
confidence: 99%
“…Although a number of agents, most notably herpes simplex virus 2, have been suspected of playing a role in cervical cancer, recent attention has focused on human papiUomavirus (HPV) as a possible etiologic agent in the genesis of CIN and invasive cancer. Immunologic and nucleic acid hybridization studies have demonstrated the presence of HPV structural antigens, DNA, or both in a high proportion of benign, premalignant, and malignant lesions of the cervix [2][3][4]. The discovery and molecular cloning of HPV types 16 and 18 from invasive cervical cancers [5,6], and the subsequent demonstration of the presence of these and closely related virus DNAs in the majority of CIN II-III lesions, invasive cervical cancers, cervical cancer lymph node metastases, and cervical cancer cell lines strongly suggests a causal relationship [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%